Association Between Carotid Artery Perivascular Fat Density and Embolic Stroke of Undetermined Source - Hu, Xiaohong; Chen, Jianhui; Fu, Huajun; Chen, Yinjuan; Fan, Daofeng; Chen, Yangui; Shen, Chaoxiong (Frontiers in Neurology, 2022)
Aim This study aims to retrospectively evaluate the association between pericarotid inflammation and the presence of embolic stroke of undetermined source (ESUS). Methods In total, 126 patients with ESUS and 118 patients with ischemic stroke from large artery atherosclerosis (LAA) were enrolled. All the patients underwent brain MRI and a neck CT angiography (CTA) examination. Reviewers were blinded to infarct location and stroke cause. Paired t-tests assessed within-subjects differences in mean Hounsfield units (HUs) in carotid perivascular fat between the cerebral infarction side and contralateral side for ESUS and LAA ischemic stroke cases. The unpaired Student's t-test was used to assess between-subjects differences in mean HUs between ESUS and LAA ischemic stroke cases. Results In both the ESUS cases and LAA ischemic stroke cases, the pericarotid fat density around the carotid artery ipsilateral to the stroke significantly increased compared with contralateral stroke position in both the groups (ESUS cases −56.31 ± 18.70 vs. −67.31 ± 20.01, p = 0.000; LAA ischemic stroke cases −51.62 ± 19.95 vs. −64.58 ± 22.68, p = 0.000). However, there was no significant difference in ipsilateral and contralateral positions to infarct between ESUS cases and LAA ischemic stroke cases (ipsilateral to infarct −56.31 ± 18.70 vs. −51.62 ± 19.95, p = 0.059; contralateral to infarct −67.31 ± 20.01 vs. −64.58 ± 22.68, p = 0.320). Conclusion We found increased density in the fat surrounding carotid artery ipsilateral to stroke compared with contralateral in ESUS, suggesting the presence of an inflammatory reaction that extends beyond the vessel lumen in patients with ESUS with a risk factor profile similar to LAA strokes.